Use of Drama to Enhance Speaking Skills of English as a Second Language (ESL) Learners (Sudurpaschim Spectrum, 2023)
This study delves into the transformative potential of Shakespearean drama staging in enhancing the speaking skills of English as a Second Language (ESL) learners in higher education. Employing a qualitative interpretive research paradigm and drawing on Vygotsky’s sociocultural theory, the research utilizes semi-structured interviews as the primary tool to explore the experiences of teachers and students in a specific Department of English Language and Literature at a private university in Chattogram, Bangladesh. The findings illuminate the manifold benefits of drama, including heightened speaking confidence, improved teamwork, enhanced improvisational skills, and increased self-esteem. This study not only contributes valuable insights into the advantages of incorporating Shakespearean dramas in ESL settings but also establishes a foundation for future research in diverse contexts beyond national borders.